Strategi Pembangunan Sumber Daya Manusia Berbasis Pembangunan Desa Untuk Meningkatkan Kesejahteraan Masyarakat Desa - Hayat Hayat; Slamet Hidayat Turohman; Yaqub Cikusin (Jurnal Transformasi Administrasi, 2018)
The purpose of this study is to determine the implementation of human resource development based on the Minister of Home Affairs No. 114 of 2014 About Village Development Guidelines in Tungkulrejo Village, Padas Sub-district, Ngawi District. To Know the Supporting and Inhibiting Factors in the Implementation of Human Resource Development in Tungkulrejo Village, Padas Sub-district, Ngawi District. This research uses field research method which gives description about the implementation of human resource development in Tungkulrjo Village, Padas Subdistrict, Ngawi Regency. Data collection techniques use observation, interview or documentation techniques, by selecting subjects and informants who are involved and technically and functionally involved in human resource development. The data obtained are then analyzed qualitatively. The results of this study illustrate that; The role of village government in the development of human resources in Tungkulrejo Village, has made policy on activities that can build existing human resources. However, these activities have not been able to provide a good impact on the economy of the people of Tungkulrejo Village. Internal and external factors become an inhibiting and supporting factor in the development of human resources in Tungkulrejo Village.